SASBat audio steganography using Bat-Algorithm-based OLSB substitution with PGP encryption - Viñas, Vina T. (2015)
Through the years, digital multimedia applications have rapidly developed. Alongside this, secure data transmission has become the main issue in data communication system so several data hiding techniques have been developed to ensure the security of a data transfer. Audio steganography, which is a technique used to transmit hidden information by modifying an audio signal in an imperceptible manner, is one of the methods used today to ensure the security of data transfer between the sender and the recipient.